Золотой ключик, или Приключения Буратино - Толстой Алексей Николаевич (Омич, 1992)
Экземпляры: ДО (20210629) / Инвентарный номер: 61829 / Цена: 05.00 / Авт.знак: Т52 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6